Preparation and characterization of (CuInTe2)1-x(TaTe)x solid solutions (0<x<1) - Grima Gallardo, P. (2018)
Polycrystalline samples of the (CuInTe2)1-x(TaTe)x alloys system were prepared by the melt and anneal technique in the composition range 0 < x < 1. Products were characterized by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Differential Thermal Analysis (DTA) and SQUID techniques. From XRD and SEM, it was found that the solubility of TaTe in CuInTe2 is around 10%; however, samples up to x = 2/3 are composed by a mean tetragonal CuInTe2-like phase with traces of Ta2Te3. Samples with x > 2/3 show diffraction patterns with several phases with poor crystallization. In addition, the tetragonal CuInTe2-like phase shows spinodal decomposition i.e. there are two phases, one Ta-rich and the other Ta-poor, with the same crystal structure and very close lattice parameters. SEM measurements also show up to six different phases, although they do not produce observed diffraction line in powder XRD patterns. DC magnetic susceptibility measurements as a function of temperature using the ZFC-FC protocol were performed in samples with x ≤ 2/3. With the exception of x = 2/3, all samples show a similar behavior in the ZFC and FC curves which are typical of a system with a distribution of magnetic cluster sizes. Sample x = 2/3 shows ferromagnetic behavior with Tc = 50 K. For sample x = 1/4, measurements of the magnetization as a function of the applied magnetic field and temperature were performed. From the analysis of the curves it was found that the clusters contain 105 Ta-atoms and a coercitive field of 0.22 kOe at T = 5 K.